LITERATUR REVIEW : EFEKTIVITAS PLATELET-RICH PLASMA TERHADAP PERBAIKAN ORGAN GINJAL - Linda Chiuman; Chrismis Novalinda Ginting (Jurnal Maternitas Kebidanan, 2021)
Kidney Failure is a health condition that worsen the quality of life. In Acute Kidney Injury and Chronic Kidney Disease there is a damage not only in function but also in the structure of kidney. Platelet Rich Plasma is known to has a lot of benefits as a medical treatment. Platelet Rich Plasma is a plasma that rich in platelets which has the function of regenerating and repairing tissue structures, especially damaged kidneys. This study aimsTo determine the effectiveness of Platelet-Rich Plasma on the improvement of  damaged kidneys. This paper uses a literature study or literature review by searching through Google Scholar or Pubmed using the keywords “Platelet-Rich Plasma”, “Acute Kidney Injury”, “Chronic Kidney Disease” for the last 5 years studies published between 2016 to 2021. Based on the literature search, there were 5 research articles related to the effectiveness of Platelet Rich Plasma on the improvement of damaged kidney, where all studies were tested on experimental animals. Based on the results of the literature study, it can be concluded that there is a relationship between the effectiveness of Platelet-Rich Plasma on the improvement of damaged kidneys in experimental animals.